Improving Motoric Skills Through Busy Book Media for 4-5 Year Old Children at Aisyiyah Kindergarten 17 Jasem, Ngoro District: Peningkatan Kemampuan Motorik Halus Melalui Media Busy Book Untuk Anak Usia 4-5 Tahun Di Taman Kanak-Kanak Aisyiyah 17 Jasem Kecamatan Ngoro - Rif’atul Hasanah; Evie Destiana (Inquest Journal, 2022)
Motoric skills have an important role in the lives of early childhood because with the presence of fine motor skills children can use various stationery equipment that will be needed in everyday life. Based on research at Kindergarten Aisyiyah 17 Jasem, Ngoro Regency, some children have not developed optimally in fine motor use, especially in group A aged 4-5 years. This study aims to improve fine motor skills in children. Lacking this, this research uses Classroom Action Research which is carried out in 2 cycles. This research was conducted in three stages, namely pre-: pre-cycle, cycle I, to get the expected results. In the pre-cycle most of the children still got an average score of 39%, while in the first cycle the percentage score increased so that the percentage score became 69%, which means that it is less than optimal. Then the researcher continued by giving action in cycle II, after the research cycle II the percentage of the average score of children became 81.25%, so that the average ga cycle I and cycle II increased again. This can be seen from the comparison between cycle I and cycle II during the study. From the results obtained, there is an increase which proves that proves than improve fine motor skills in children.